2019
DOI: 10.17475/kastorman.543538
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Photosystem II Photochemical Efficiency and Biomass Partitioning in Acacia mellifera and Acacia laeta Seedlings Under Drying Soil

Abstract: Aim of study: The study aimed to assess the impact of drying soil on diurnal photochemical efficiency of photosystem II and biomass partitioning of the seedlings of Acaia mellifera (Mf) and Acacia laeta (Lt).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It is common in the arid African savanna. It grows on hard clay soil in the central parts of Sudan and extends westward to near Lake Chad [15]. Acacia mellifera has the ability to x nitrogen, which is thought to improve soil fertility and, ultimately, herbage quality under canopy and beyond [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is common in the arid African savanna. It grows on hard clay soil in the central parts of Sudan and extends westward to near Lake Chad [15]. Acacia mellifera has the ability to x nitrogen, which is thought to improve soil fertility and, ultimately, herbage quality under canopy and beyond [16].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent understanding of young seedling growth and capacity of photosynthetic machinery under water stress conditions likely provides us information to select the appropriate genotypes for plantation in dry lands. It has been reported that the assessment of plant morphogenesis at early stages of life provides necessary indicators for subsequent performance of species under arid environments (Johnson, 1980;Kramer and Boyer, 1995;Merine et al, 2015;Siam and Abdalkreem., 2019). In an ecophysiological context, the measurement of chlorophyll fluorescence tends to be a useful technique in quantification the effect of stresses on photochemical efficiency of PSII (Klughammer and Schreiber, 2008;Lambers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%